Analisis Hybrid DSS untuk Menentukan Lokasi Wisata Terbaik - Annisak Izzaty Jamhur Nisa; Radius Prawiro; Novi Trisna (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
Tourism is an activity carried out by humans to a place alone or together to have fun to get rid of the burden of thoughts that were previously acquired. The Mandeh area is a leading tourist area in West Sumatra which has 10 alternative tourist attractions. With the many tourist locations in the area, tourists are confused about what places to visit in the Mande area. In this study, a combined analysis or Hybrid Decision Support System (DSS) was carried out using a combination of the Analytical Hierarchy Process (AHP) method with the Simple Additive Weighting (SAW) method. The purpose of this research is to be able to combine AHP and SAW methods in one DSS analysis and then be able to recommend the decision results to tourists in the form of the best tourist locations in the Mandeh area. With the recommendation, it can increase the interest of tourists to come and increase the opinions of tourist location owners and the surrounding community. The result of this research is to obtain a recommendation for the best tourist location decision in the Mande area of ​​West Sumatra, namely the location of Manjunto Beach with the highest value of 0.895.